1987
DOI: 10.1111/j.1476-5381.1987.tb11203.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of morphine on cardiovascular responses to acute myocardial ischaemia in rats

Abstract: 1The effects of acute coronary artery ligation on cardiac rhythm and haemodynamics were studied in rats receiving either acute or chronic morphine-treatment. 2 In chronic opiate-treated animals, increasing concentrations of morphine sulphate were administered in drinking water over a 3 week period, and the development of morphine tolerance and dependence was verified by decreased analgesic responses to morphine in the tail-immersion test and the occurrence of naloxone-precipitated withdrawal syndromes, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…These include altered sensitivity to the actions of catecholamines, acetylcholine, 5-hydroxytryptamine and arachidonic acid (Schulz & Goldstein, 1973;Kromer & Steigeman, 1982;Rae & De Moraes, 1983;Dai et al, 1985;Martin & Takemori, 1986) and altered responses to certain pathophysiological conditions such as acute myocardial ischaemia (Chan et al, 1987;Ko et al, 1988). The mechanisms behind such effects are not clear.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…These include altered sensitivity to the actions of catecholamines, acetylcholine, 5-hydroxytryptamine and arachidonic acid (Schulz & Goldstein, 1973;Kromer & Steigeman, 1982;Rae & De Moraes, 1983;Dai et al, 1985;Martin & Takemori, 1986) and altered responses to certain pathophysiological conditions such as acute myocardial ischaemia (Chan et al, 1987;Ko et al, 1988). The mechanisms behind such effects are not clear.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…In the chronic study, a previously described method for inducing opiate dependence (Badawy et al, 1982;Chan et al, 1987) was adopted for chronic administration of morphine. Rats, weighing 250-300 g, were used.…”
Section: Morphine Treatmentmentioning
confidence: 99%
“…It has been found in a recent study that rats undergoing chronic morphine-treatment exhibit significantly lower incidence and delayed onset of early ventricular arrhythmias during acute myocardial ischaemia (Chan et al, 1987). However, the mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that, depending on the species and opioid-exposure time, experimental animals also exhibit other physiological alterations after chronic opiate treatment which are different from those observed after acute treatment (Schulz & Goldstein, 1973; Kromer & Steigemann, 1982; Rae & De Moraes, 1983;Dai et al, 1985;Martin & Takemori, 1 Author for correspondence. 1986). Recently, it has been observed that chronically morphine-treated rats exhibit a significantly lower incidence and delayed onset of early ventricular arrhythmias, and a marked decline in ventricular noradrenaline concentration, during acute myocardial ischaemia (Chan et al, 1987;Ko et al, 1988). A previous study has shown that the cardiovascular responses to sympathetic nerve stimulation are significantly reduced following prolonged morphine administration (Leung et al, 1986b).…”
Section: Introductionmentioning
confidence: 99%